Answer:
(-5,1)
(-2,4)
Explanation:
y = x + 6
y = x^2 + 8x + 16
Since both equations are equal to y, we can set them equal to each other
x + 6 = x^2 + 8x + 16
Subtract x from each side
x -x + 6
= x^2 + 8x-x + 16
6 = x^2 +7x +16
Subtract 6 from each side
6-6 = x^2 +7x +16-6
0 = x^2 +7x +10
Factor
What 2 numbers multiply together to give us 10 and add together to give us 7?
5*2 = 10
5+2 =7
0 = (x+5) (x+2)
Using the zero product property
x+5 = 0 x+2 = 0
x = -5 x=-2
Now we need to find the y's that go with the x's
x=-5
y= x+6
y =-5+6
y=-1
(-5,1)
x=-2
y = -2+6
y=4
(-2,4)